The official ARRSE guide to the British Army what it is and how it works - Astor, Des (Bantam Press, 2011)
The up-to-the minute, irreverent (but extremely informative) insider's guide to the British Army today. How will they defeat the Taliban and bring peace to Afghanistan? What will the British soldier of the late 21st century look like? When will the next World War break out? We're damned if we know, but if you want to find out what today's British Army is really like, then this is the book for you. Drawn from the wit and wisdom of the Army Rumor Service, Britain's biggest and most active military website, this guide gives the inside track on all aspects of modern British military life. How do I join? Where will I be sent? What's the hardware like? What exactly is it that clerks put in staff officers' coffee? Why do the RAF wear uniforms? Where can I get a decent pair of boots? Is there any meat in an army sausage? All these crucial questions-and more-will be answered by the Official Arrse Guide.